Investigating PBL’s Effect on Critical Thinking by Cognitive Style: A Quasi-Experimental Study - Ismi Indriani Bahtiar; Hikmatul Khusna (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Critical thinking skills enable individuals to analyze various perspectives before reaching a conclusion, resulting in more appropriate and successful actions. FI and FD cognitive styles influence how students process information, with FI students tending to be more analytical and independent, while FD students are more dependent on context and external assistance in understanding the material. This research aims to: 1) To investigate the outcome of the impact of PBL method for evaluating students critical thinking abilities, 2) to investigate the variation among FI and FD cognitive styles of students in relation to their critical thinking abilities in the PBL model- applied class. This research employed a quantitative method based on a quasi- experimental configuration with a non-equivalent control group design involving 71 high school students. Data analysis techniques used t-tests and effect size calculations. The conclusion of this research suggest that: 1) The PBL model did not significantly improve students' critical thinking abilities, with the obtained effect size classified as moderate, 2) After learning with the PBL method, compared to students with FD cognitive styles, those with FI cognitive styles had noticeably superior critical thinking skills., where the average score for FI students was higher than that for FD students.